Pedagogical Practice As A Means Of Forming A Future Teacher - Babayan, Izabella; Sisyan, Susanna (Զանգակ հրատ.)
The content of any educational process must be progressive and derive from the primary goal of forming, teaching, and educating the essential abilities, capacities, and skills for the future specialist, as well as the value system, guided not by the level and requirements of the educational sector but by the educational system. In other words, the student should be viewed from the development perspective. Pedagogical practices have an irreplaceable role in turning the knowledge acquired in the pedagogical university into abilities and in acquiring important professional qualities for the teacher, bearing in mind that the pedagogical profile of the teacher is completed during the pedagogical practical work. Pedagogical practice is one of the most critical components of pedagogical education, which aims to form and develop future educators' general and professional competencies. To understand the current issues of Pedagogical practice as an essential means of forming the professional abilities of the future teacher and aim to help improve that process in the context of university education, we conducted research. We explored the process of organizing Pedagogical practice, tested its effectiveness, and developed recommendations for increasing the effectiveness of pedagogical practice.
Keywords: Pedagogy